Evaluation of Intubation Prediction Score for assessment of Difficult Intubation: A Prospective Observational Study - Tiwari, Ashish Raj; Shakya, Bigen Man; Bista, Navindra Raj; Pradhan, Bishwas (Nepal Journal of Medical Sciences, 2024)
Introduction: Endotracheal intubation is an airway management technique indicated in various clinical situations which can be challenging at times. Proper planning is paramount in these situations. An unanticipated difficult airway can lead to improper management which may potentially cause severe complications including irreversible brain damage or death. Prediction of difficult airways, thus, has great importance. The study was conducted to assess the intubation prediction score (IPS) as an airway assessment tool for the prediction of difficult visualization of the larynx. Methods: Eighty-eight American Society of Anaesthesiologists Physical Status I and II patients undergoing elective surgery requiring general anaesthesia with endotracheal intubation were enrolled in this prospective, observational study. Airway assessment of the patients was done preoperatively with different tests included in Intubation prediction score. After induction of anaesthesia and achieving adequate muscle relaxation, laryngoscopy was done by consultant anaesthesiologist unaware of the score. Modified Cormack-Lehane grading (MCLG) after optimal external laryngeal manipulation during laryngoscopy was recorded as the standard test for difficult intubation prediction. The sensitivity, specificity, positive predictive value, negative predictive value, and likelihood ratios were calculated. Results: The prevalence of difficult intubation was 17.1%. The sensitivity, specificity, PPV, NPV, positive and negative LR of IPS were 78.6%, 63.2%, 30.6%, 93.5%, 2.14, and 0.34 respectively. Conclusions: Intubation prediction score which is combination of commonly used test for airway assessment has a sensitivity of 78.6% and a specificity of 63.2% for the prediction of difficult intubation.